Pengaruh pengampunan pajak, pemahaman peraturan perpajakan, pemahaman akuntansi, kualitas pelayanan fiskus terhadap kepatuhan wajib pajak dengan preferensi risiko sebagai variabel moderating - Leviana, Martha; Adriani, Ade; Norlena, Norlena (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of this research is to discover the influence of tax amnesty, tax regulations understanding, accounting understanding, fiscal service on taxpayer compliance with risk preference as a moderating variable. The population on this research is Corporate Taxpayer (Entity Taxpayer) which is still active. There are 100 Corporate Taxpayer questioners as the sample. This research applied SEM PLS (SmartPLS3) as the research method. The results of the study indicate that tax amnesty, understanding of tax regulations, understanding of accounting, quality of tax service services have a significant effect on taxpayer compliance, risk preferences are able to moderate the effect of understanding tax regulations on taxpayer compliance, but risk preferences cannot moderate the effect of tax amnesty, the effect of between the understanding of accounting, the influence of the quality of tax services on taxpayer compliance.